2023
DOI: 10.3390/plants12193465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Environment on Species Diversity of Desert Plant Communities

Jie Sun,
Nai’ang Wang,
Zhenmin Niu

Abstract: Desert ecosystems possess an astonishing biodiversity and are rich in endangered species. This study investigated characteristics of species diversity and soil environmental factors in three major deserts of China’s Alxa Plateau. The Alxa Desert included 183 plant species belonging to 109 genera and 35 families. The highest numbers of plant species belonged to the Compositae, Gramineae, and Chenopodiaceae families. The research area belongs to the semi-shrub and small semi-shrub deserts in temperate deserts. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the arid regions of Northwest China, natural environmental factors such as salinity, temperature, and precipitation play pivotal roles in shaping the potential geographic distribution and growth development of species [ 17 , 20 , 44 , 46 ]. The findings from this study revealed that elevation, salinity, and temperature significantly influenced the distribution patterns of E. equisetina , E. intermedia , and E. monosperma .…”
Section: Discussionmentioning
confidence: 99%
“…In the arid regions of Northwest China, natural environmental factors such as salinity, temperature, and precipitation play pivotal roles in shaping the potential geographic distribution and growth development of species [ 17 , 20 , 44 , 46 ]. The findings from this study revealed that elevation, salinity, and temperature significantly influenced the distribution patterns of E. equisetina , E. intermedia , and E. monosperma .…”
Section: Discussionmentioning
confidence: 99%
“…Soil is the environmental basis for the survival of terrestrial plants, and it plays an important role in the formation and development of the structure and function of plant communities; it is also an important environmental factor that affects the productivity and biodiversity of plant communities [ 10 , 11 ]. Plant communities and soil environments are interconnected and interact with each other through physical and chemical processes, which are important for maintaining the stability of the ecosystem structure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%